Strategic Location Management in the Banking Industry: Evidence from a Commercial Bank in Semarang - Mustika Widowati; Windi Novia Ratri Wardhani; Nita Hernita (Universitas Pekalongan, 2026)
This study aims to analyze strategic location management and its role in supporting competitive advantage and service performance in the banking industry. The research focuses on Bank Permata Hati operating in Semarang, a major economic hub in Central Java, where competition among banks is increasingly intense. Using a quantitative case-based approach, primary data were collected through questionnaires distributed to branch managers and operational staff, complemented by secondary data from internal reports and regional statistics. Strategic location management is measured through accessibility, proximity to customers, surrounding business activities, and infrastructure availability, while bank performance is assessed using service efficiency, customer growth, and transaction volume indicators. Data were analyzed using descriptive statistics and multiple regression analysis. The results show that strategic location management has a positive and significant effect on bank performance. Branches located in areas with high accessibility, dense economic activity, and adequate infrastructure demonstrate better service performance and higher customer acquisition rates. The findings imply that location strategy is not merely an operational decision but a strategic resource that supports sustainable competitive advantage in the banking sector. This study contributes to strategic management and banking literature by providing empirical evidence from a regional context and offers practical insights for bank management in optimizing branch location decisions.